The influence of transketolase on lipid biosynthesis in the yeast Yarrowia lipolytica - Adam Dobrowolski (Microbial Cell Factories, 2020)
Abstract Background During the pentose phosphate pathway (PPP), two important components, NADPH and pentoses, are provided to the cell. Previously it was shown that this metabolic pathway is a source of reducing agent for lipid synthesis from glucose in the yeast Yarrowia lipolytica. Y. lipolytica is an attractive microbial host since it is able to convert untypical feedstocks, such as glycerol, into oils, which subsequently can be transesterified to biodiesel. However, the lipogenesis process is a complex phenomenon, and it still remains unknown which genes from the PPP are involved in lipid synthesis. Results To address this problem we overexpressed five genes from this metabolic pathway: transaldolase (TAL1, YALI0F15587g), transketolase (TKL1, YALI0E06479g), ribulose-phosphate 3-epimerase (RPE1, YALI0C11880g) and two dehydrogenases, NADP+-dependent glucose-6-phosphate dehydrogenase (ZWF1, YALI0E22649g) and NADP+-dependent 6-phosphogluconate dehydrogenase (GND1, YALI0B15598g), simultaneously with diacylglycerol acyltransferase (DGA1, YALI0E32769g) and verified each resulting strain’s ability to synthesize fatty acid growing on both glycerol and glucose as a carbon source. Our results showed that co-expression of DGA1 and TKL1 results in higher SCO synthesis, increasing lipid content by 40% over the control strain (DGA1 overexpression). Conclusions Simultaneous overexpression of DGA1 and TKL1 genes results in a higher lipid titer independently from the fermentation conditions, such as carbon source, pH and YE supplementation.